The influence of MgO on the physical, structural, mechanical, optical, and radiation absorption properties of the boro-germanate glass system - Sayyed, M.I.; Kaky, Kawa M.; Mhareb, M.H.A.; A Imheidat, Mohammad; Es-soufi, H.; Jawad Kadhim, Abed; Baki, S.O. (Elsevier, 2024)
To study non-traditional glass materials, this investigation created four glass samples composed of (70-x)B2O3–20TeO2-10GeO2-xMgO, where x represents the percentage of MgO with values of 20, 25, 30, and 35 mol%. Glasses with high transparency were produced via the accepted melt quenching and annealing method. The samples underwent X-ray diffraction analysis to confirm their glassy structure. Fourier transform infrared spectroscopy was utilized to examine the glass network's various structural groups. The measuring methodology and theoretical calculations were used to calculate a range of physical and mechanical parameters. The cut-off wavelength, as well as the direct and indirect bandgap, and other optical characteristics of the S1–S4 samples were observed using optical absorption. The work utilized Phy-X to acquire the ionizing absorption parameters. The paper demonstrates various glasses' radiation shielding properties, including the effective atomic number, half- and tenth-value layers, linear attenuation coefficient, mass attenuation coefficient, and mean free path.